Facile preparation of chemically stable metal mesh-based superamphiphobic surface toward effective anti-adhesion - Yinyu Sun; Zihan Yin; Caiyun Shen; Wei Yang; Qi Chen; Yu Liu; Zhongcheng Ke; Changjiang Li (AIP Advances)
Superamphiphobic materials that possess extraordinary hydrophobic and oleophobic dual characteristics have aroused widespread attention for their application in the fields of self-cleaning, petroleum industry, and antifouling. However, the synthetic process is a formidable challenge. Herein, this paper provides a simple method for preparing superamphiphobic materials on the base of stainless steel metal mesh (SSM). CuO nanoclusters (CuO-NCs) were fabricated in situ on the surface of SSM to obtain CuO-NCs@SSM by immersion–burning method, followed by solution deposition method to coat the silane fluoride group (SFG) on CuO-NCs@SSM (SFG@CuO-NCs@SSM). SFG@CuO-NCs@SSM possesses brilliant superhydrophobic and superoleophobic properties with the static contact angle of water, diesel oil, glycerin, corn oil, and liquid paraffin droplets of 153°, 152°, 153°, 152°, and 151°, respectively. The sample also shows excellent anti-adhesion, from which the falling water can automatically take away the powder attached to the surface of the material. When the sample was immersed in liquid paraffin, the mirror phenomenon will appear. Moreover, the material remains dry on the surface after taking out from the solutions of liquid paraffin or muddy water. In addition, the sample has excellent high temperature resistance and acid/alkaline resistance. The chemical durability tests display that SFG@CuO-NCs@SSM can remain superamphiphobic under chemical damages, including high temperatures (25–200 °C) and acid/alkaline solutions (pH = 1–14). In this paper, the fabrication process of SFG@CuO-NCs@SSM can be extended to different metal materials, which has enormous range of application potential prospects.